1996
DOI: 10.1007/s001010050318
|View full text |Cite
|
Sign up to set email alerts
|

Ist die Elimination von Osteosarkomzellen durch ?maschinelle Autotransfusion? und LeukozytenDepletionsfilter m�glich?

Abstract: The sole use of the autotransfuser DIDECO BT 795/P during osteosarcoma surgery is not recommended because of the potential danger of retransfusion of malignant cells. In combination with the leukocyte depletion filter PALL BPF 4, no osteosarcoma cells were identified in the red cell concentrate. Since the adhesiveness of tumor cells from established cell lines may be different from that of tumor cells in the intraoperative salvaged blood, further studies with blood from the surgical field are necessary to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…The filtration efficacy in terms of cancer cell reduction using a newer generation of LDFs is 99.6% [60] to 99.9% [61]. This was demonstrated for a large variety of tissues such as prostate and renal cancer [62]; osteosarcoma [63]; breast [64]; colorectal [65]; pancreatic [23]; hepatocellular [66]; endometrium, cervical, and ovarian [67]; spinal metastases [68]; and lung cancer [69].…”
Section: Discussionmentioning
confidence: 99%
“…The filtration efficacy in terms of cancer cell reduction using a newer generation of LDFs is 99.6% [60] to 99.9% [61]. This was demonstrated for a large variety of tissues such as prostate and renal cancer [62]; osteosarcoma [63]; breast [64]; colorectal [65]; pancreatic [23]; hepatocellular [66]; endometrium, cervical, and ovarian [67]; spinal metastases [68]; and lung cancer [69].…”
Section: Discussionmentioning
confidence: 99%
“…(1994 ), using a Dideco Autotrans BT 725, Sepacell R‐500 filters and COLO 38 cells, estimated that 92.5% of the cells were removed in the washing stage and then showed that the remaining 7.5% were removed by filtration. Müller et al . (1996 ), using osteosarcoma cells and Pall BF4 filters, showed similar results.…”
Section: Fields Containing Malignant Tissuementioning
confidence: 99%
“…However, clinical evaluations have not found adverse effects of IAT on tumor recurrence or survival 34,41,42 , but no large outcome trials have been completed. The insertion of different leukocyte-depleting filters into the IAT processing loop has been advocated repeatedly to reduce the probability of spreading tumor cells, but results are controversial 34,[43][44][45][46][47][48] . More recently, the irradiation of the erythrocyte suspension retransfusate with 50 Gy has shown promising results 47,48 .…”
Section: Contraindicationsmentioning
confidence: 99%